Wind tunnel tests of stratospheric airship counter rotating propellers. Issue 1 (January 2015) - Chen, Yaxi; Liu, Peiqing; Tang, Zhihao; Guo, Hao
Abstract: Aerodynamic performance of the high-altitude propeller, especially the counter rotation effects, is experimentally studied. Influences of different configurations on a stratospheric airship, included 2-blade counter-rotating propeller (CRP), dual 2-blade single rotation propellers (SRPs) and 4-blade SRP, are also indicated. This research indicates that the effect of counter rotation can greatly improve the efficiency. It shows that the CRP configuration results in a higher efficiency than the dual 2-blade SRPs configuration or 4-blade SRP configuration under the same advance ratio, and the CRP configuration also gains the highest efficiency whether under the situation of providing the same trust or absorbing the same power. It concludes that, for a stratospheric airship, the CRP configuration is better than the multiple SRPs configuration or a multi-blade SRP one.